2018
DOI: 10.1073/pnas.1718659115
|View full text |Cite
|
Sign up to set email alerts
|

T cell receptors for the HIV KK10 epitope from patients with differential immunologic control are functionally indistinguishable

Abstract: HIV controllers (HCs) are individuals who can naturally control HIV infection, partially due to potent HIV-specific CD8+ T cell responses. Here, we examined the hypothesis that superior function of CD8+ T cells from HCs is encoded by their T cell receptors (TCRs). We compared the functional properties of immunodominant HIV-specific TCRs obtained from HLA-B*2705 HCs and chronic progressors (CPs) following expression in primary T cells. T cells transduced with TCRs from HCs and CPs showed equivalent induction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…However, some studies have shown reduced recognition of L6M by KK10-specific T cells (Chen et al, 2012; Iglesias et al, 2011; Xia et al, 2014). In our previous study, L6M mutation did not affect cytotoxicity when target cells were pulsed with saturating amounts of the peptide (Joglekar et al, 2018). Cytotoxicity assays using GXR-B27 cells infected with wildtype or L6M mutant viruses showed attenuated recognition of L6M (Fig 4B).…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…However, some studies have shown reduced recognition of L6M by KK10-specific T cells (Chen et al, 2012; Iglesias et al, 2011; Xia et al, 2014). In our previous study, L6M mutation did not affect cytotoxicity when target cells were pulsed with saturating amounts of the peptide (Joglekar et al, 2018). Cytotoxicity assays using GXR-B27 cells infected with wildtype or L6M mutant viruses showed attenuated recognition of L6M (Fig 4B).…”
Section: Resultsmentioning
confidence: 89%
“…Two B*27:05-KK10-specific TCRs, EC27 and EC5.5 (referred to as FC5.5 previously), isolated from HIV controllers were used for immunotherapy (Joglekar et al, 2018). The TCRs were cloned into lentiviral vectors and linked to a cell surface marker, LNGFR, using 2A peptide sequences.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations